Family-Assisted Severity of Illness Monitoring for Hospitalized Children in Low-Resource Settings—A Two-Arm Interventional Feasibility Study - von Saint Andre-von Arnim, Amelie O.; Kumar, Rashmi K.; Clark, Jonna D.; Wilfond, Benjamin S.; Nguyen, Quynh-Uyen P.; Mutonga, Daniel M.; Zimmerman, Jerry J.; Oron, Assaf P.; Walson, Judd L. (Frontiers in Pediatrics, 2022)
Introduction: Pediatric mortality remains unacceptably high in many low-resource settings, with inpatient deaths often associated with delayed recognition of clinical deterioration. The Family-Assisted Severe Febrile Illness ThERapy(FASTER) tool has been developed for caregivers to assist in monitoring their hospitalized children and alert clinicians. This study evaluates feasibility of implementation by caregivers and clinicians. Methods: Randomized controlled feasibility study at Kenyatta National Hospital, Kenya. Children hospitalized with acute febrile illness with caregivers at the bedside for 24 hours were enrolled. Caregivers were trained using the FASTER tool. The primary outcome was the frequency of clinician reassessments between intervention (FASTER) and standard care arms. Poisson regression with random intercept for grouping by patient was used, adjusting for admission pediatric early warning score, age, gender. Secondary outcomes included survey assessments of clinician and caregiver experiences with FASTER. Results: 150 patient/caregiver pairs were enrolled, 139 included in the analysis, 74 in the intervention, 65 in the control arm. Patients’ median age was 0.9 (range 0.2-10) and 1.1 years (range 0.2-12) in intervention versus control arms. The most common diagnoses were pneumonia (80[58%]), meningitis (58[38%]) and malaria (34[24%]). 134(96%) caregivers were patients’ mothers. Clinician visits/hour increased with patients’ illness severity in both arms, but without difference in frequency between arms (point estimate for difference -0.9%, p=0.97). Of the 16 deaths, 8 (four/arm) occurred within 2 days of enrollment. Forty clinicians were surveyed, 33(82%) reporting that FASTER could improve outcomes of very sick children in low-resource settings; 26(65%) rating caregivers as able to adequately capture patients’ severity of illness. Of 70 caregivers surveyed, 63(90%) reported that FASTER training was easy to understand; all(100%) agreed that the intervention would improve care of hospitalized children and help identify sick children in their community. Discussion: We observed no difference in recorded frequency of clinician visits with FASTER monitoring. However, the tool was rated positively by caregivers and clinicians. Implementation appears feasible but requires optimization. These feasibility data may inform a larger trial powered to measure morbidity and mortality outcomes to determine the utility of FASTER in detecting and responding to clinical deterioration in low-resource settings.